IMF Staff papers : Volume 31 No. 1. (IMF Staff Papers; IMF Staff Papers ;, 1984)
This paper studies the role of domestic and foreign savings in financing capital formation in 19 industrial countries during the years after World War II. The authors' interpretation of the statistical evidence is that there is very little support for the view that, over the medium term, goods and services freed by savings in one industrial country are systematically made available through current account imbalances to finance investment in physical capital in other industrial countries. The study also finds little support for the view that the integration of financial capital markets in recent years has altered the relationships among domestic savings, investment, and current account imbalances in industrial countries. The evidence suggests that changes in net foreign assets, and the associated current account imbalances, were no more sensitive to cross-country differences in rates of return on physical capital in the ten years ending in 1981 than they had been in the 1950s, when extensive capital controls and trade restrictions hampered the economic integration of the industrial countries.